2015
DOI: 10.1016/j.cegh.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of delay in the health care seeking behaviour of STD patients

Abstract: c l i n i c a l e p i d e m i o l o g y a n d g l o b a l h e a l t h 3 ( 2 0 1 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…This similarity might be due to the similarity of sample size, design and study population. The finding of this study was also in line with studies conducted in Kerala of India (41.9%) [27],…”
Section: Discussionsupporting
confidence: 92%
“…This similarity might be due to the similarity of sample size, design and study population. The finding of this study was also in line with studies conducted in Kerala of India (41.9%) [27],…”
Section: Discussionsupporting
confidence: 92%
“…The way such choices are made and the factors driving them have attracted many researchers. Previous studies indicated that the choice of hospitals is affected by several factors, such as personal preferences and interests (13, 15), service cost (3, 1622), type and severity of the disease (13, 14, 18, 2326), waiting time to receive services (22, 27), location and distance between the place of residence and the hospital (3, 9, 13, 1620, 22, 2831), availability of advanced medical equipment and technology (3, 13, 2225, 29, 32), having health insurance (16, 2325), interpersonal skills, and employees’ behavior (3, 16, 28, 3335), physician’s expertise (16, 27, 29), hospital reputation (3, 16, 17, 22, 28, 34), service quality (3, 18, 20, 3436), diversity and method of service provision (3, 16, 21), and patient’s economic capacity (13, 18, 2326, 37). Several studies indicate that most people tend to choose qualified physicians and hospitals with a high reputation, regardless of the type and severity of their diseases in a context where citizens have full freedom (13).…”
Section: Introductionmentioning
confidence: 99%
“…Only half in India [ 21 ], and 35% in Ghana [ 22 ] seek care for the sexually transmitted diseases. Based on different studies; delay in seeking care for sexually transmitted diseases were related to high wealth index, presences of offensive odor, perception of symptoms as normal, feeling shay, lack of female health workers, distance to facility, lack of availability of treatments, having non-ulcerative STDs, age, religion, occupational status, and type of family [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%